Penerapan Model Pembelajaran Discovery Learning Dalam Meningkatkan Hasil Belajar Ipa Materi Perubahan Kenampakan Pada Bumi Dan Benda Langit Siswa Kelas Iv Sd Negeri 3 Gaden Trucuk Klaten - Sulastri, Sulastri (Universitas Sebelas Maret, 2022)
This type of research is quantitative. The population in this study were all fourth grade students at SD Negeri 3 Gaden, totaling 60 students consisting of control class students and experimental class students. By using a sampling technique, namely saturated samples. The research design used is Pretest-Posttest Control Group Design in the form of Control Group Design. Based on the results of research data analysis after receiving treatment using the Discovery Learning model, the results of this research show that there is a difference in the control class pretest score and the experimental class pretest score, then a posttest was carried out with the control class average score being 80.33 while the class average score experimentally amounted to 83.43 as proven by the t test results, namely t tcount > ttable, namely 2.00865 > 2.000. This means that there is an increase in students' pretest results before being given treatment, with students' posttest results after being given treatment with the Discovery Learning learning model which can reach the Minimum Completeness Criteria (KKM), namely 75 and classical learning completeness reaches 90%. Therefore, it can be concluded that the Discovery Learning learning model is effective on science learning outcomes regarding Changes in the Appearance of the Earth and Heavenly Bodies in class IV students at SD Negeri 3 Gaden Trucuk Klaten.